Cryopreservation in Presence of PEG-1500 Affects Erythrocyte Surface Characteristics - Zemlianskykh, Nina G.; Babiychuk, Lyubov A. (Problems of Cryobiology and Cryomedicine, 2015)
The studies of changes in surface characteristics of erythrocyte membranes caused by freeze-thawing can be important for assessment of structural and functional integrity of cells and understanding the mechanisms responsible for their damage under extreme conditions. In the research we studied the effect of cryopreservation in presence of exocellular cryoprotectant PEG-1500 on asymmetric distribution of phosphatidylserine in membrane and characteristics of the surface marker CD44 in erythrocyte suspension (the amount of CD44-positive cells and the expression level). It was found that cell amount with the impairments of transmembrane asymmetry of phosphatidylserine increased up to 30% after a short-term exposure of frozen-thawed erythrocytes at 37Â°C. The decrease in CD44-positive cell amount and lowering of the marker expression were also observed in cryopreserved erythrocyte suspension. Washing of erythrocytes from the cryoprotectant and hemolysis accompanying this process led to restoration of CD44 parameters in suspension of erythrocytes which preserved their integrity. The revealed impairments of surface characteristics of erythrocytes indicate a presence of sublethal membrane injuries in the cells cryopreserved under the protection of PEG-1500. This was true, at least in terms of the changes in the surface marker CD44 indices, since after lysis of cells compromised with sublethal injuries occured during removal of cryoprotectant, the marker indices in erythrocyte suspension did not differ from the control values. Probl Cryobiol Cryomed 2015; 25(2): 104-113